High pressure synthesis of a quasi-one-dimensional GdFeO3-type perovskite PrCuO3 with nearly divalent Cu ions. Issue 61 (10th July 2019) - Ito, Masaharu; Takahashi, Hidefumi; Sakai, Hideaki; Sagayama, Hajime; Yamasaki, Yuichi; Yokoyama, Yuichi; Setoyama, Hiroyuki; Wadati, Hiroki; Takahashi, Kanako; Kusano, Yoshihiro; Ishiwata, Shintaro
Abstract : A new perovskite-type cuprate PrCuO3 with unusual oxidation state and quasi-one-dimensional Cu–O chains has been synthesized by high-pressure oxygen annealing. Abstract : A new perovskite-type cuprate PrCuO3 has been synthesized by high-pressure oxygen annealing. Synchrotron X-ray powder diffraction and absorption spectroscopy revealed that PrCuO3 crystallizes in the GdFeO3 -type structure with cooperative Jahn–Teller distortion, forming one-dimensional chains of corner-shared CuO4 plaquettes with nearly divalent Cu ions.